A comprehensive review of biodiesel and CNG as alternative fuels for compression ignition engine. (2018) - Pathak, Sudhir Kumar; Thakur, Amrit Kumar; Nayyar, Ashish; Kumar, Chandan
In the substitution of alternative fuels for compression ignition (CI) engines, several investigations and review studies have been done in the last few years. This paper presents a broad review on the production, performance and emissions of biodiesel and compressed natural gas (CNG) as replacement to fossil-based diesel fuel for CI engines. The properties of biodiesel and CNG, produced from altered sources and their fatty acid composition have also been addressed. The summary of experimental set-up used by different researchers for the studies and performance and emissions characteristics of CI engines with biodiesel is present in this paper. The complete impression of this paper is that the performance of the engine slightly depreciates with the use of biodiesel and CNG partially instead of diesel, but the emissions are significantly improved. The impressive cetane number and the inherent oxygen of biodiesel improve the combustion process which leads to reductions in HC, CO and smoke formation. When CNG is using as an alternative fuel the soot and NOx emissions are decreasing for CI engines.